2023
DOI: 10.1111/1365-2435.14269
|View full text |Cite
|
Sign up to set email alerts
|

Seed dormancy revisited: Dormancy‐release pathways and environmental interactions

Abstract: 1. Many internal (inherent) and environmental (imposed) factors control seed dormancy and germination that we divide into three basic dormancy-release pathways: Maternal structures and embryo physiology control inherent dormancy that is broken by various types of scarification and physiological changes, followed by imposed-dormancy release when the prevailing environment is replaced by certain 'standard' conditions that stimulate germination (Pathway 1); imposed dormancy prevails even if inherent dormancy is b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 117 publications
1
14
0
Order By: Relevance
“…Both paternal drought and maternal drought had negative effects on seed production of P. ostii , with maternal drought exhibiting a stronger influence (Figure 2). Our results generally are consistent with previous studies that found the paternal effect on seed development and seed mass is smaller than the maternal effect (Baskin & Baskin, 2019; Lacey, 1996; Lamont & Pausas, 2023). This is because maternal drought not only reduces the potential for zygote formation and increases embryo abortion, but it also decreases maternal provisioning.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Both paternal drought and maternal drought had negative effects on seed production of P. ostii , with maternal drought exhibiting a stronger influence (Figure 2). Our results generally are consistent with previous studies that found the paternal effect on seed development and seed mass is smaller than the maternal effect (Baskin & Baskin, 2019; Lacey, 1996; Lamont & Pausas, 2023). This is because maternal drought not only reduces the potential for zygote formation and increases embryo abortion, but it also decreases maternal provisioning.…”
Section: Discussionsupporting
confidence: 93%
“…Possibly this is due to the significant role of nuclear genes in regulating photosynthesis-related phenomena despite the maternal inheritance of chloroplasts (Stern et al, 2004). Overall, the somewhat larger number of performance traits affected by interaction with maternal environments appears to be small compared to the much larger maternal dosage in the endosperm, maternally derived nuclear genes or maternal contribution to the embryo's cytoplasm (Kong et al, 2020;Lacey, 1996;Lamont & Pausas, 2023;Roach & Wulff, 1987).…”
Section: Effect Of Maternal Paternal and Offspring Drought On Offspri...mentioning
confidence: 99%
See 2 more Smart Citations
“…Naturally, the seed's outer shell abrades mechanically and chemically in the gastrointestinal tract of an animal [27,28]. Some species also need to experience extreme heat or freeze to trigger germination [29].…”
Section: Discussionmentioning
confidence: 99%